Ethics in Qualitative Research - Grande Ratti, María F.; Murature, Delfina; Sánchez Del Roscio, Agustín; Frei, Salomé; Benitez, Sonia E. (Revista del Hospital Italiano de Buenos Aires, 2024)
Ethical considerations are essential to ensure that any research project takes place responsibly, respecting the rights and well-being of participants and maintaining scientific integrity. This article presents the safeguards of qualitative research, emphasizing bioethical principles and the handling of personal data. Researchers must implement rigorous measures to ensure confidentiality. That includes obtaining informed consent from participants before collecting personal data, using secure methods for data storage and transmission, and ensuring that data protection measures prevent data from being used in a way that could identify identity. When interviews are the collection method, they should consider the implications of audio recordings (voice recognition) and video recordings (image protection). The collected data may be sensitive and reveal delicate information about individuals, so verbatims must be anonymized.